Elucidating the microscopic origin of observed anti-correlation between the protein-protein and protein-water interaction energies - Krishnendu Sinha; Amit Kumawat; Suman Chakrabarty (Chemical Physics Impact, 2024)
Water as a solvent plays an important role in dictating the structure and dynamics of the large biomolecules like proteins. It has been proposed that the protein dynamics and energetics are closely coupled to the water molecules in the hydration shell. In particular, it has been shown earlier that the fluctuations in intra-protein (protein-protein) interaction energy is strongly anti-correlated with the protein-water interaction energy (solvation energy). Moreover, the dynamical signatures of water gets reflected into the protein dynamics in terms of a dominant power law behavior. In this work, we have carried out systematic molecular dynamics (MD) simulations of three different protein systems to understand the key physical factors that contribute to such anti-correlations. First, we compare the dynamics in globular folded proteins like Lysozyme with intrinsically disordered peptides (IDPs) like Amyloid beta to show that enhanced conformational fluctuations lead to significantly stronger anti-correlation. Trp-cage miniprotein shows a similar behavior distributed over two sub-ensembles of folded and unfolded states. We also investigate what type of interactions and molecular processes are responsible for the observed anti-correlation. In particular, we observe that the extent of correlation decreases significantly in the order of charged, polar and non-polar amino acid residues. Charged residues that form salt bridge interactions show a dominant anti-correlation. Surprisingly, a few non-polar (hydrophobic and buried) residues demonstrate significant anti-correlation as well. We attribute this to the structural fluctuations that lead to an equilibrium between buried and solvent exposed states of these residues, where the protein-protein and protein-water interactions compensate each other. Our studies indicate that the molecular origin of the observed anti-correlation can be vary depending on the type of the interaction. The overall coupling/correlation is dominated by the electrostatic interactions and charged residues due to a general dielectric screening effect, whereas a few buried hydrophobic residues may also show such coupling due to structural dynamics between buried and exposed states.